Evaluasi Terhadap Pelaksanaan Pendidikan Anak Usia Dini di KB Indah Mulya Indralaya (Sekolah Tinggi Agama Buddha Nalanda, 2023)
This research conducts an evaluation of the implementation of Early Childhood Education at KB Indah Mulya Indralaya. The study aims to assess the effectiveness and quality of the Early Childhood Education program, considering various factors such as curriculum delivery, teaching methodologies, infrastructure, and overall learning environment. Through a combination of qualitative and quantitative research methods, including surveys, interviews, and classroom observations, the evaluation seeks to identify strengths, weaknesses, and areas for improvement in the current implementation of Early Childhood Education at KB Indah Mulya Indralaya. The findings of this study contribute valuable insights to enhance the overall educational experience for young learners in the specified context.